Blinde Flecken im Mediensystem? Qualitätsjournalismus im Krisenmodus - Hug, Theo; Penz, Jasmin (innsbruck university press, 2023)
Blind Spots in the Media System? What criteria can be used to measure journalistic quality in times of crisis? How can reporting be balanced or ""objective"" if every piece of information in the case of conflicts, crises or wars can always also be seen as a partisan factor? To what extent may journalists go too far, and which reporting patterns contribute to the well-being of a democratic and pluralistic public? The contributions to the edited volume ask about the possibilities and limits of a conflict-sensitive journalism that does not want to give up quality claims of balanced reporting, reliable information and multi-perspective offers of orientation even in difficult times.